2002
DOI: 10.1002/ana.10148
|View full text |Cite
|
Sign up to set email alerts
|

Interferon β‐1a for early multiple sclerosis: CHAMPS trial subgroup analyses

Abstract: The objective of this work was to assess the effect of interferon beta-1a (Avonex) on the rate of development of clinically definite multiple sclerosis and brain magnetic resonance imaging changes in subgroups based on type of presenting event, baseline brain magnetic resonance imaging parameters, and demographic factors in the Controlled High-Risk Subjects Avonex Multiple Sclerosis Prevention Study (CHAMPS) trial. After the onset of a first demyelinating event, 383 patients with brain magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 15 publications
6
76
1
1
Order By: Relevance
“…We found a 23.8% 5 year risk of developing MS, a value in accordance with previous reports, which estimate MS conversion rates between 10% and 30% in these patients [3][4][5][6][7][8][9]. The Optic Neuritis Treatment Trial [3], the largest study on MS risk after ON, included 191 patients with ON without baseline brain MRI lesions, with a conversion risk in this subgroup of 16% at 5 years, 22% at 10 years and 25% at 15 years, suggesting higher risk of MS development in the first 5 years and very low probability of conversion after 10 years of follow-up.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found a 23.8% 5 year risk of developing MS, a value in accordance with previous reports, which estimate MS conversion rates between 10% and 30% in these patients [3][4][5][6][7][8][9]. The Optic Neuritis Treatment Trial [3], the largest study on MS risk after ON, included 191 patients with ON without baseline brain MRI lesions, with a conversion risk in this subgroup of 16% at 5 years, 22% at 10 years and 25% at 15 years, suggesting higher risk of MS development in the first 5 years and very low probability of conversion after 10 years of follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, when assessing and managing a patient with isolated ON without an identifiable etiology, the possibility of future development of MS has to be considered. Determining which patients have a higher risk of conversion to MS is important, as studies suggest that there may be a benefit from early immunomodulatory treatment in patients with clinically isolated syndrome (CIS), including ON [4][5][6][7][8][9][10]. Although the presence of one or more lesions on baseline brain MRI has been identified as the strongest predictor of MS conversion [3,[11][12][13][14][15][16], there are patients with normal baseline MRI who also develop MS and predictors of conversion are still to be determined in this subgroup of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria selected for patients with active clinical and MRI disease. Subgroup analyses demonstrated more pronounced effects in those with more disease activity [30]. Regression to the mean, an issue that continues to plague more recent MS trials, posits that variables that are extreme on the first measurement will tend to be close to the average on the second measurement.…”
Section: Clinically Isolated Syndromementioning
confidence: 98%
“…That spinal cord CIS patients with abnormal brain studies are at high risk for experiencing a second clinical attack was confirmed in a subgroup analysis of the CHAMPS clinical trial, a randomized, blinded, placebo-controlled study of the impact of once-weekly interferon b-1a on the risk of conversion from an initial demyelinating event to CDMS (Beck et al, 2002). Eighty-three enrolled patients presented with spinal cord CIS and had two or more brain lesions typical of MS. Forty-one received interferon b-1a and 42 received placebo.…”
Section: Clinically Isolated Spinal Cord Syndrome and Risk Of Msmentioning
confidence: 87%
“…In recent clinical trials of patients presenting with a clinically isolated syndrome (CIS) who also had abnormalities on brain MRI consistent with MS, spinal cord presentations constituted 19-22% of cases (Beck et al, 2002;Polman et al, 2008). These and other studies showed that disease-modifying therapies used for the treatment of MS were effective in delaying the time to a second clinical attack in patients who presented with CIS and who had brain MRI scans suggestive of MS (Filippi et al, 2004;Comi et al, 2009).…”
Section: Clinically Isolated Spinal Cord Syndrome and Risk Of Msmentioning
confidence: 94%